Principles of age-related changes in the canine and feline brain - Papaioannou Nikolaos (Sciendo, 2014)
In the aged dog and cat, especially dog, a cognitive decline develops naturally in many different domains, but at the same time it also exhibits human-like individual variability in the aging process. In the aging dog and cat brain lesions develop spontaneously. Dogs share some morphological characteristics with those of Alzheimer’s disease in man. The canine brain with its plaques and tangles which show oxidative changes, forms a spontaneous model for understanding the early changes and their interrelationships in Alzheimer’s disease. Additionally, the aged dog represents a useful model for the development of preventive or therapeutic interventions to improve aged brain function. These interventions can then be translated into human clinical trials.